Arts of address : being alive to language and the world - Roelofs, Monique (Columbia themes in philosophy, social criticism, and the arts., 2020)
"Monique Roelofs offers a pathbreaking systematic model of the field of address and puts it to work in the arts, critical theory, and social life. She shows how address props up finely hewn modalities of relationality, agency, and normativity. Address exceeds a one-on-one pairing of cultural productions with their audiences. As ardently energizing tiny slippages and snippets as fueling larger impulses in the society, it activates and reaestheticizes registers of race, gender, class, coloniality, and cosmopolitanism. In readings of writers and artists ranging from Julio Cortázar to Jamaica Kincaid and from Martha Rosler to Pope. L, Roelofs demonstrates the centrality of address to freedom and a critical political aesthetics. Under the banner of a unified concept of address, Hume, Kant, and Foucault strike up conversations with Benjamin, Barthes, Althusser, Fanon, Anzaldúa, and Butler. Drawing on a wide array of artistic and theoretical sources and challenging disciplinary boundaries, the book illuminates address's significance to cultural existence and to our reflexive aesthetic engagement in it"--